Violence et histoire dans les séries télévisées : Introduction - Sylvie Allouche (Cahiers d’histoire.)
The four series analyzed focus on the victims of history, namely various populations who have suffered physical or social violence, aggravated by symbolic violence as the dominant versions of history tend to ignore or minimize their roles or the sufferings and injustices they have endured: women involved in the tumult of France’s recent history (Isabelle Veyrat-Masson on Maria Vandamme and Sonia Suvélor on Les Combattantes), Indians of North America (Martin Shuster on Yellowstone), Hutu civilians who took refuge in Congo (Sylvie Allouche on Black Earth Rising). We hope to offer readers an original approach to this question, and more broadly to enable them to better understand certain issues of historical series.